SOME ASPECTS OF WOMEN’S PARTICIPATION IN RELIGIOUS EXTREMISM AND TERRORISM (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the dynamics and changing trends of women's participation in religious extremism and terrorism. The study examines the socio-economic and psychological factors that contribute to the involvement of women in radical movements, as well as their role in preventing extremism. Special attention is paid to state policies and social initiatives aimed at countering the spread of extremist ideologies among women. The findings highlight the importance of preventive and educational measures in addressing radicalization processes.
Keywords: women, religious extremism, terrorism, radicalization, social factors.